2014
DOI: 10.1074/jbc.m114.567040
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Yin Yang 1 Oligomers That Cooperate with RuvBL1-RuvBL2 ATPases

Abstract: Background: Oligomerization of transcription factor YY1 is not well understood. Results: YY1 assembles homo-oligomers that bind DNAs without the consensus sequence, whose structure is studied by electron microscopy. Conclusion: RuvBL1-RuvBL2 enhances YY1 binding to DNAs without the consensus sequence for the transcription factor. Significance: YY1-RuvBL1-RuvBL2 complexes could contribute to functions beyond transcription, and we find this occurs during homologous recombination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 48 publications
6
45
0
Order By: Relevance
“…To confirm that YY1 dimerization occurs, FLAG-tagged and HA-tagged versions of YY1 protein were expressed in cells, nuclei were isolated and the tagged YY1 proteins in nuclear extracts were immunoprecipitated with either anti-FLAG or anti-HA antibodies. The results show that the FLAG-tagged and HA-tagged YY1 proteins interact (Figures 1G, 1H, S1I, and S1J), consistent with prior reports that YY1 proteins oligomerize (López-Perrote et al, 2014). Other highly expressed nuclear proteins such as OCT4 did not co-precipitate, indicating that the assay was specific (Figure S1J).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…To confirm that YY1 dimerization occurs, FLAG-tagged and HA-tagged versions of YY1 protein were expressed in cells, nuclei were isolated and the tagged YY1 proteins in nuclear extracts were immunoprecipitated with either anti-FLAG or anti-HA antibodies. The results show that the FLAG-tagged and HA-tagged YY1 proteins interact (Figures 1G, 1H, S1I, and S1J), consistent with prior reports that YY1 proteins oligomerize (López-Perrote et al, 2014). Other highly expressed nuclear proteins such as OCT4 did not co-precipitate, indicating that the assay was specific (Figure S1J).…”
Section: Resultssupporting
confidence: 91%
“…Of 26 transcription factors that occupy both enhancers and promoters (Figure 1A), four (CTCF, YY1, NRF1, and ZBTB11) are essential based on a CRISPR cell-essentiality screen (Figure 1B) (Wang et al, 2015) and two (CTCF, YY1) are expressed in >90% of tissues examined (Figure 1C). YY1 and CTCF share additional features: like CTCF, YY1 is a zinc-finger transcription factor (Klenova et al, 1993; Shi et al, 1991), essential for embryonic and adult cell viability (Donohoe et al, 1999; Heath et al, 2008) and capable of forming homodimers (López-Perrote et al, 2014; Saldaña-Meyer et al, 2014) (Table S1). YY1, however, tends to occupy active enhancers and promoters, as well as some insulators, whereas CTCF preferentially occupies insulator elements (Figures 1D and S1A–S1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The affinity of the YY1 ZFs in our EMSAs does appear to be somewhat lower than in EMSAs of the full-length protein to RNA sequences of comparable length (23). Additionally, it has been suggested that full-length YY1 forms a homo-oligomer, allowing YY1 to bind DNA sequences lacking the cognate recognition site (42), and it is possible that YY1 oligomerisation also influences RNA specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Assembly of INO80 and TIP60 has been shown to be dependent on the RUVBLs [46], [47]. In addition, RUVBLs enhance the DNA binding ability of YY1, a transcription factor that canonically associates with INO80 [48]. This evidence suggests that the RUVBL proteins are required members of remodeler assemblies that exist to enhance binding efficiency and specification at epigenetic docking sites, similar to BAF53A.…”
Section: Accessory Subunits In Remodeler Activitiesmentioning
confidence: 99%